(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Аbstrаct: The dynamic character of online discourse communities, where a variety of linguistic practices thrive across platforms like social media and internet forums, is reflected in the language variance found in digital communication.